Inclusive Education In The Lebanese Educational System - Basma Frangieh; Serge Ramel (The Journal of Studies in Language, Culture and Society)
As a founding member of the United Nations, Lebanon aims to include its educational policy in the UN‟s Sustainable Development Goal (SDGs), in particular the fourth, which aims to ensure "inclusive and equitable quality education and promote lifelong learning opportunities for all". To achieve this objective at the national level, many structures and systems have been created in schools, particularly in the private sector. The nature of the interventions and the support offered are not similar, while the room for manoeuvre is not the same for all schools (Akiki & Frangieh, 2018). The structures and systems in Lebanon for the education of students with special educational needs (SEN) then vary from the most segregated schooling to the least restrictive. A systematic review methodology (Young & Eldermire, 2017) was applied. The work and projects related to inclusive education in Lebanon were analysed. It shows that inclusive education remains work in progress without a global action plan. This work dynamic encourages both local initiatives and generates difficulties in carrying them out. Our results show that the development of inclusive education in Lebanon is marked by uncertainties, tensions and contradictions.